Metaanaliza v biomedicini - Kastrin, Andrej (Informatica Medica Slovenica, 2008)
Meta-analysis refers to the statistical analysis of a large collection of independent observations for the purpose of integrating results. The benefits of meta-analysis include more effective exploitation of existing data from independent sources and contribution to more powerful domain knowledge. Meta-analysis is one of the most popular techniques in modern biomedical sciences in order to combine, analyze, and interpret the results of clinical studies. Some epistemiological issues are first reviewed. We highlight major historical landmarks of metaanalysis and its statistical background. We conclude with comprehensive directions of metaanalysis of microarray experiments.
Keywords: biomedicina; metaanaliza; Meta-analiza; Meta-Analysis; Raziskava; Research; statistična analiza